PLANNING STUDY OF INTERNAL LIGHTNING OVERVOLTAGE PROTECTION ON 1,5 MW SOLAR POWER PLANT AT TANJUNGPURA UNIVERSITY - Simbolon, Gerry (Telecommunications, Computers, and Electricals Engineering Journal (TELECTRICAL), 2025)
Solar power generation is an electric power generation system that converts sunlight energy into electrical energy. Currently, Tanjungpura University is building a 1.5 MW solar power plant with a land area of 11,075 m^2. This research aims to design an internal lightning protection system that is capable of protecting of the solar power plant Tanjungpura University 1.5 MW so that the solar power generation system can be protected from overcurrent due to indirect lightning strikes. In this internal lightning protection system design research, a combination box and AC switchgear panel will be designed to protect the solar power plant system. In the combination box a DC protection system will be installed in the form of a fuse, Miniature Circuir Breaker (MCB), and Surge Protection Device (SPD). Meanwhile, in AC switchgear panels, the AC protection systems that will be used are Molded Chase Circuit Breaker (MCCB), Surge Protection Device (SPD) and Air Circuit Breaker (ACB). From the results of these calculations, a design for an internal lightning protection system was created for the solar power plant 1.5 MW electricity at Tanjungpura University which was installed in a combiner box and AC switchgear panel.